Mechanical Cardiopulmonary Resuscitation (CPR) Is Better Than Manual CPR? Literature Study - Wijaya, Sapondra; Susmini, Susmini; Soewito, Bambang; Wibowo, Wahyu Dwi Ari (Jurnal Surya, 2024)
Introduction: Mechanical CPR mitigate rescuer fatigue and ensure adherence to guidelines, potentially enhancing overall survival rates. Contrarily, manual CPR relies on human skill, presenting challenges in maintaining uniformity and endurance. Unveiling the complexities within this juxtaposition becomes imperative in shaping future resuscitative paradigms. The purposeof studi is to determine the effectiveness of mechanical CPR in cardiac arrest management compared to manual CPRMethods: Database used were Pubmed and Proquest using the keywords "Mechanical CPR", "Automatic CPR Device" and "Cardiac Arrest". The inclusion criteria were last 5 years published, analyzing the effect of automatic CPR devices on cardiac arrest management, as well as full text articles. The inclusion criteria are literature review, systematic review or is not original research. The number of articles eligible for review is 10 journal articlesResults: The use of automatic CPR equipment is still inferior compared to manual CPR during cardiac arrest with the use value being 4-5% of all cardiac arrest patients. There are 4 journals that state that ROSC in cardiac arrest management using automatic CPR devices is higher than manual, but there are 2 journal articles that report the opposite. Automatic CPR device is very vulnerable to injury with fractures reaching 85.5% of total injuries compared to manual CPR which does not experience injury.Conclusion: The use of automatic CPR device does not produce better results than manual CPR overall for ROSC, but is very useful and meaningful in certain conditions such as during the transportation process, therefore, the automatic CPR device is more meaningful for pre-hospital useKeywords: Manual CPR; Mechanical CPR; CPR; OHCA